Balikbayang sinta an E. San Juan reader - San Juan, Epifanio 1938- (Quezon City Ateneo de Manila University Press, 2008)
"Balikbayang Sinta: An E. San Juan Reader" represents an epoch-making anthology of San Juan's recent interventions into cultural studies in this stage of corporate-led globalization. From his pioneering introduction of George Lukac's essays, Marxism and Human Liberation (1972), to his engagement with the debate of racial formations in the last decades of the twentieth century, San Juan has inserted the Philippines into the contemporary discourse on the crisis of the humanities and modern letters. hailed as a scholar of world-historical significance, San Juan sums up forty years of critical reflection on the burning topics of his time in this gathering of essays and interviews that aims to provoke debate on the issue of whether humanity will choose capitalist barbarism or socialism as the future of the planet."--Back cover.
Reflections on postcolonial theory and postmodernity : an interview -- Imperialist war on terrorism and the responsibility of cultural studies -- Freedom and human rights under imperialist hegemony -- Rizal in the USA : escaping the Anglo quarantine, reinventing "Los Indios Bravos" -- Parallel lives : Carlos Bulosan and Philip Vera Cruz -- Inventing vernacular speech acts : articulating Filipino self-determination in the United States -- Carlos Bulosan : critique and revolution -- Writing and the Asian diaspora : an interview -- Ordeals of indigenization : on sikolohiyang Pilipino -- Souvenirs from the Diliman period -- Remapping the Filipino diaspora in the age of globalization -- "Sa loob at labas ng bayan kong sawi" : emergency signals from a Filipino exile.
Keywords: History, Modern -- 20th century; Philippine essays (English).; Philippines -- Politics and government; Philippines -- Social conditions -- 20th century